Enhancing Students’ Vocabulary Mastery by Using First Letter Card Media at the First Semester Students of Accounting at State Islamic Institute (IAIN) Parepare - Nurul Hasanah; Syahban Mada Ali (JURNAL EDUKASI NONFORMAL, 2021)
The objective of the research was to find out whether the students’ vocabulary of Accounting for Islamic Financial Institutions IAIN Parepare are enhancing through First Letter Card Media or not. The researcher applied Quantitative method (pre-experiment). The population was the students of Accounting for Islamic Financial Institutions at First semester. This research applied cluster random sampling by taking one class as the sample that was the Class B First semester students of Accounting for Islamic Financial Institutions. The sample consisted of 30 students. The data were collected through Vocabulary test. The result of this research showed that the Vocabulary of first semester students of Accounting for Islamic Financial Institutions IAIN Parepare were enhancing by using First Letter Card Media.